Design and application of the layered soil moisture monitor for the smart agriculture - Xiaoqiang ZHAO; Heng QUAN; Zhufeng YAN; Lujun WANG (物联网学报)
With the rapid development of the smart agriculture in China,the soil moisture monitoring has become particularly important.But there exist many problems in current monitoring methods,such as difficulties in layout and installation,electrode interference,and single monitoring depth.A soil moisture monitor suitable for the farmland was designed.For the hardware structure,a tube-type non-contact design scheme was adopted,and multiple modules were designed in order to realize the layered non-contact monitoring.For the software protocol,a control strategy of the multi-node access based on the Modbus protocol was proposed,which had the characteristics of high polling efficiency,data stability,and wide monitoring nodes.The data was transmitted to the cloud server through the message queuing telemetry transport (MQTT) protocol for the agricultural analysis and decision-making.The test in the vineyard area shows that the monitor can monitor the moisture content in the range of 0~100% and accuracy of ± 2.45%,which is of certain stability and practicality.